2013
DOI: 10.1016/j.pain.2013.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Daily repetitive transcranial magnetic stimulation of primary motor cortex for neuropathic pain: A randomized, multicenter, double-blind, crossover, sham-controlled trial

Abstract: There is little evidence for multisession repetitive transcranial magnetic stimulation (rTMS) on pain relief in patients with neuropathic pain (NP), although single-session rTMS was suggested to provide transient pain relief in NP patients. We aimed to assess the efficacy and safety of 10 daily rTMS in NP patients. We conducted a randomized, double-blind, sham-controlled, crossover study at 7 centers. Seventy NP patients were randomly assigned to 2 groups. A series of 10 daily 5-Hz rTMS (500 pulses/session) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
136
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(143 citation statements)
references
References 36 publications
4
136
0
3
Order By: Relevance
“…Moreover, this method can be easily applied to patients in non-invasive, randomized and blinded studies. These features distinguish this method from other non-invasive interventional tools, such as transcranial direct current stimulation39 and transcranial magnetic stimulation40. Although these modalities change cortical activity and excitability to relieve pain41, it is difficult to control the information represented in the patterns of cortical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this method can be easily applied to patients in non-invasive, randomized and blinded studies. These features distinguish this method from other non-invasive interventional tools, such as transcranial direct current stimulation39 and transcranial magnetic stimulation40. Although these modalities change cortical activity and excitability to relieve pain41, it is difficult to control the information represented in the patterns of cortical activity.…”
Section: Discussionmentioning
confidence: 99%
“…78 A randomized double-blind, sham-controlled, crossover study (7 centers, n 5 70 patients) concluded that daily multisession (10 sessions) high-frequency (5 Hz) rTMS of M1 provides short-term and modest pain relief in patients with neuropathic pain. 79 Therefore, lowfrequency (1 Hz or 5 Hz) rTMS of M1 is unlikely to induce significant beneficial effects in terms of pain control compared with high-frequency (10 Hz or 20 Hz) stimulation (Table 1). 76,80 rTMS of Other Cortical Areas for Chronic Pain…”
Section: Rtms Of M1 For Chronic Painmentioning
confidence: 99%
“…After reviewing the full texts, we deemed 8 English language studies that enrolled 459 patients with CPSP eligible for our review (Table 1). [37][38][39][40][41][42][43][44] There was almost perfect agreement (Φ=0.82) between reviewers at the full-text review stage. All trials evaluated treatment effects on pain, and none reported effects on physical functioning, role functioning, or interpersonal functioning (Figure 2).…”
Section: Resultsmentioning
confidence: 99%